The Metaphorical Talk About Corruption in the Bulgarian Media Discourse - Pencheva, Antonia (Research Papers, 2020)
Corruption is a persistent social problem of modern times, hence it continues to be in the limelight for society at large, the nation state, the international organizations and commits them to making efforts to resolve all corruption-related issues. In a number of articles it has been highlighted that as a result of its the global dimensions, corruption has increasingly make been perceived as one of the serious threats in the contemporary world.This paper analyzes the corruption-based conceptual metaphors in media and political discourse. The journalistic texts transmit the anti-corruption measures that political parties suggest or that state-run bodies take, while imposing a mode of interpretation of the phenomenon by society.The metaphorical models analyzed under four headings – anthropomorphic, sociomorphic, nature-morphic and artefact metaphors – expose the universal and culture-specific character of the interpretation of corruption in the Bulgarian national mind. It is highly relevant that these models should be revealed, given that "they can all influence public opinion and shape public attitudes to the important events and individuals in the contemporary life in Bulgaria" (Tsoneva, 2012). The specific cases analyzed in the paper expose the tools through society is impacted emotionally and rationally in the era of post-truth. These tools are based on the "text and talk" about the fight against corruption, which largely has replaced the effective counteraction of corruption.